2021
DOI: 10.1002/adfm.202106174
|View full text |Cite
|
Sign up to set email alerts
|

Solid Electrolyte with Oxidation Tolerance Provides a High‐Capacity Li2S‐Based Positive Electrode for All‐Solid‐State Li/S Batteries

Abstract: The electrochemical window of solid electrolytes (SEs) plays a crucial role in designing active material-SE interfaces in high-energy-density all-solidstate batteries (ASSBs). However, the suitable electrochemical window for individual active materials is not yet investigated, as the electrochemical window of SEs is overestimated. In this study, the oxidation onset voltages (OOVs) of several SEs, namely those compatible with Li 2 S as a high-capacity positive electrode material are determined. Results reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 88 publications
(126 reference statements)
3
42
0
Order By: Relevance
“…The Li 2 S–LiI–C cell shows a higher capacity than that of the Li 2 S–LPS–C cell, which suggests that LiI is superior to LPS as an ionic conduction pathway, although LPS itself has a higher conductivity than LiI. Previously, we reported that the oxidation onset voltage of a nanosized ionic conduction pathway contributes to the charge–discharge capacity, and this experiment is consistent with our previous paper. Therefore, this positive electrode can be used to investigate the origin of the high utilization and full reversibility of the all-solid-state Li 2 S–LiI–C cell because it excludes the influence of the sulfide SE, including the contributions of the total capacity, reaction distribution, and overlapping peaks in the S2p XPS.…”
Section: Resultssupporting
confidence: 91%
“…The Li 2 S–LiI–C cell shows a higher capacity than that of the Li 2 S–LPS–C cell, which suggests that LiI is superior to LPS as an ionic conduction pathway, although LPS itself has a higher conductivity than LiI. Previously, we reported that the oxidation onset voltage of a nanosized ionic conduction pathway contributes to the charge–discharge capacity, and this experiment is consistent with our previous paper. Therefore, this positive electrode can be used to investigate the origin of the high utilization and full reversibility of the all-solid-state Li 2 S–LiI–C cell because it excludes the influence of the sulfide SE, including the contributions of the total capacity, reaction distribution, and overlapping peaks in the S2p XPS.…”
Section: Resultssupporting
confidence: 91%
“…18 In addition, LiX is found as one of the decomposition products, which has been recently proved to enhance the oxidative stability of thiophosphate, Li 3 PS 4 . 27 Clearly, the substitutions via the halide anion or substitution of the cation in PS 4 3− units do not significantly affect the stability of these sulfide argyrodite solid ionic conductors. To shed light on the relation between the electronic structure and electrochemical stability, we take a closer look at the contributions of all atoms to the band edges.…”
Section: Practical Electrochemical Stabilitymentioning
confidence: 95%
“…24−26 Although the former option has shown to be very effective, it is unclear if substitution in sulfide solid electrolytes can enhance their stability toward the electrode materials for operation. Further, recent reports have explored the role of electronically insulating additives to improve electrochemical stability of thiophosphates; 27 however the reason behind enhanced stability is not clear yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid the decomposition of organic solvents, replacing the electrolyte solution with a solid electrolyte also could improve the electrochemical performance of the Li|VS4 battery. 75,76 Therefore, we recommend reducing the reactivity at the VS4/carbonate solvent interface or replacing the carbonate solvents to improve the lifetime of the Li|VS4 battery.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%